(untitled) (Research, Society and Development, 2019)
From the analysis of the film Mary and Max, the present study aims to present a playful way of promoting the rehabilitation of children diagnosed with ASD, proposing the creation of a box containing activities based on the Portfolios of Didactic and Pedagogical Materials, which aim to work the functions cognitive aspects of perception, attention, memory and language. First, a bibliographic mapping of the scientific evolution regarding the studies of autism, as well as its cognitive and diagnostic aspects, was carried out, thus showing the specific characteristics of this disorder. Based on this, a proposal was made to construct play activities to stimulate the cognitive functions of children with ASD in order to assist in cognitive assessment and rehabilitation.